80.3k views
4 votes
Match each operation involving f(x) and g(x) to its answer

Match each operation involving f(x) and g(x) to its answer-example-1

2 Answers

1 vote

Answer:

(g-f) (-1)=
√(15)

(f/g)(-1)= 0

(g+f)(2) =
√(3)-3

(g*f)(2) =
-3 √(3)

Explanation:

Given :


f(x)=1-x^2\\g(x)=√(11-4x)

To find :
(g-f)(-1)

Solution :


g(x)-f(x)=√(11-4x)-1+x^2\\(g-f)(x)=√(11-4x)-1+x^2\\(g-f)(-1)=√(11+4)-1+1=√(15)

To find :
\left ( (f)/(g) \right )(-1)

Solution :


(f(x))/(g(x))=(1-x^2)/(√(11-4x))\\(f(-1))/(g(-1))=(1-1)/(√(11+4))=0

To find :
(g+f)(2)

Solution:


g(x)+f(x)=√(11-4x)+1-x^2\\(g+f)(x)=√(11-4x)+1-x^2\\(g+f)(2)=√(11-8)+1-4=√(3)-3

To find:
(g* f)(2)

Solution:


g(x)f(x)=(gf)(x)=√(11-4x)(1-x^2)\\(gf)(2)=√(11-8)(1-4)=-3√(3)

User Matt Montag
by
4.7k points
1 vote

Answer:

(g-f) (-1)= sqrt(15)

(f/g)(-1)= 0

(g+f)(2)=sqrt(3)-3

(g*f)(2)=-3*sqrt(3)

Explanation:

We have to eval the expressions given in the point indicated.

Lets start by the first equation

(g-f)(-1)= g(-1) - f(-1)=
√(11-4*(-1))    - 1 +(-1)^(2) =
√(15)

Now, lest continue with the others

(f/g)(-1)= f(-1)/g(-1)= (1-1)/sqrt(15)=0

(g+f)(2)=g(2)+f(2)=sqrt(3)-3

(g*f)(2)=g(2)*f(2)=sqrt(3)*(-3)=-3sqrt(3)

User Blair Davidson
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.